Salivary microbiota of periodontitis aggravates bone loss in ovariectomized rats - Wang, Nannan; Zheng, Lichun; Qian, Jun; Wang, Min; Li, Lili; Huang, Yuezhen; Zhang, Qian; Li, Yanfen; Yan, Fuhua (Frontiers in Cellular and Infection Microbiology, 2022)
The mechanisms underlying the crosstalk between periodontitis and osteoporosis remain unclear. Recently, the gut microbiota has been recognized as a pivotal regulator of bone metabolism, and oral and gut mucosae are microbiologically connected. In this study, we investigated the effects of periodontitis on osteoporosis through the oral-gut axis. The salivary microbiota of patients with periodontitis was collected and then pumped into the intestine of Sprague–Dawley rats via intragastric administration for 2 weeks. An osteoporosis model was established using ovariectomy. Changes in the maxillae and femora were evaluated using microcomputed tomography and HE staining. Intestinal barrier integrity and inflammatory factors were examined using real-time quantitative polymerase chain reaction and immunofluorescence. The gut microbiota was profiled by 16S rRNA gene sequencing. Metabolome profiling of serum was performed using liquid chromatography-mass spectrometry sequencing. Both maxillae and femora showed osteoporotic phenotypes in ovariectomized (OVX) rats. Our results confirmed that the salivary microbiota of patients with periodontitis could aggravate femoral bone resorption. In addition, intestinal inflammation was exacerbated after periodontitis salivary microbiota gavaged in OVX rats. Correlation analysis of microbiota and metabolomics revealed that lipolysis and tryptophan may be related to the bone loss induced by the salivary microbiota of patients with periodontitis. In conclusion, periodontitis can aggravate long bone loss through the oral-gut axis in OVX rats.